Resistance exercise modulates kynurenine pathway in pancreatic cancer patients - Pal, Anasua; Zimmer, Philipp; Clauss, Dorothea; Schmidt, Martina; Ulrich, Cornelia; Wiskemann, Joachim; Steindorf, Karen (International journal of sports medicine, 2021)
The aim of this study was to investigate the impact of Supervised and Home-based resistance exercise on the Kynurenine pathway in patients with pancreatic cancer who underwent surgery and chemotherapy. In the SUPPORT study, adult pancreatic cancer patients were randomized to intervention programs of 6-month (1) a Supervised moderate-to-high-intensity progressive resistance training or (2) unsupervised Home-based resistance training, or (3) to a standard care patient Control group. Serum levels of kynurenine, tryptophan and IL-6 were assessed for 32 participants before, after 3 months and after 6 months of exercise intervention. Group differences were investigated using analysis-of-covariance. Patients in the Supervised training group showed decreased levels of serum kynurenine and kynurenine/tryptophan ratio (p = 0.07; p = 0.01 respectively) as well as increased Tryptophan levels (p = 0.05) in comparison to Home-based and Control group over time. The Home-based exercise group had significant increased kynurenine and kynurenine/tryptophan ratio levels. IL-6 levels decreased over the first three months for both intervention groups as well as the Control group (Supervised: p < 0.01, Home-based: p < 0.010, Control group: p < 0.01). Supervised resistance exercise might positively regulate the Kynurenine pathway and downregulate the kynurenine/tryptophan (indicative of IDO/TDO enzyme) levels, hence modulating the immune system.
Published online: 2020-07-24
Gesehen am 11.02.2021